Answer:
uuuuuuuu yan answer diba dale hehhehe
Answer:
7.211103
Step-by-step explanation:
For:
(X1, Y1) = (-3, 4)
(X2, Y2) = (1, -2)
Distance Equation Solution:
d=(1−(−3))2+(−2−4)2−−−−−−−−−−−−−−−−−−−√
d=(4)2+(−6)2−−−−−−−−−−√
d=16+36−−−−−−√
d=5–√2
d=7.211103
:)
Answer:
3/8 4/9 42% 0.35
Step-by-step explanation:
hope this right
C=1 because you are flipping it over the line so it cant be negative
So this means W(-3x) = 3x. So it's equal to 3(-3x), which simplifies to be -9x. Whenever you have a function, it looks like f(x). f doesn't have to be the letter, it can be a, b, c, or like in this case, W. It just means the output of what W(x) is if x equals the number in the parentheses, which is -3x in this case.